PEMBERDAYAAN MASYARAKAT DALAM MEMBERIKAN KESADARAN BETAPA PENTINGNNYA PENDIDIKAN BAGI GENERASI BANGSA YANG AKAN DATANG DI DESA SIGAPITON KECAMATAN AJIBATA - Tampubolon, Kevin Pratama Hasudungan; Manalu , Ervin; Siburian, Daniel Tony E; Purba, Jhon Sufriadi (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Sigapiton is a village in Ajibata Sub-district, Toba district with an area of 70.80 km² (BPS, 2018). Sigapiton village has a total of 175 families.There are hamlets in Sigapiton village consisting of hamlet I (Lumban Butar-butar, Hamlet II (Sosor Dolok, Sosor Baringin, Lumban Nauli, Lumban Hasatan). Community Service Lectures (KPPM) are also available.Activities to provide teaching to children about the importance of education fot the nation’s generation, this activity aims to enable children to think with quality for their future. KPPM is focused on providing awarensess of how important education is for the nation’s generation, as well as the application of interdisciplinary knowledge which was carried out directly by student at the elementary school SDN 173631 The teaching activities carried out were warm-up row exercise. To commemorate Indonesia,s 79th indepence day, there wa a competition held by the head of Wajon Sirait Subdustrict, S.Pd.,M. Si, indirectly, children’s knowledge of Marching rules (PBB) Has a big impact on children for their future. The next hape is often carried out by teachers so that children feer the benefits and can understand the importance of education for children.